Caregivers Acceptance of Using Semantic Communication Boards for teaching Children with Complex Communication Needs - Pereira, Jayr A.; Pereira, Jaylton A.; Fidalgo, Robson do N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na Educação, 2021)
Alternative Communication Boards (ACB) are used to compensate for the difficulties faced by people with complex communication needs. These boards facilitate the construction of telegraphic phrases through visual cues, using colors and pictograms to represent the grammatical class and the meaning of the words, respectively. In this paper, we present the combination of three essential materials to construct a semantic ACB. In this context, a Semantic ACB is a communication board that uses a semantic script to guide the message authoring. The proposal was evaluated using the Technology Acceptance Model (TAM) as a basis. The results demonstrate that caregivers are more interested in a semantic ACB that is useful than in one that is easy to use.